Rheological behavior of an artificial synovial fluid – influence of temperature, shear rate and pressure. (March 2021) - Rothammer, Benedict; Marian, Max; Rummel, Florian; Schroeder, Stefan; Uhler, Maximilian; Kretzer, J. Philippe; Tremmel, Stephan; Wartzack, Sandro
Abstract: Despite the excellent clinical performance of joint replacements, wear-induced aseptic loosening is a main cause of premature implant failure. Tribological testing is usually carried out using bovine serum as an artificial synovial fluid. In order to gain new insights into the suitability to simulate human synovial fluid and provide recommendations for the conditions of tribological testing, accurate rheological measurements on the influence of temperature, shear rate and pressure on density and viscosity were performed. Thus, a temperature dependence of density and viscosity could be verified, whereas both values decreased with higher temperatures. The temperature dependency of viscosity could be approximated by an Arrhenius model. Moreover, shear-thinning characteristics could be demonstrated and fitted to a Cross model, which agreed well with investigations on human synovial fluid reported in literature. Furthermore, an anomaly of pressure dependence of viscosity was found and correlated with the behavior of water as a main constituent. At room temperature, the viscosity initially decreased to a minimum and then increased again as a function of pressure. This was no longer distinct at human body temperatures. Consequently, the present study confirms the suitability of bovine serum as a substitute synovial fluid and emphasizes the importance of realistic testing conditions in order to ensure transferability and comparability. Graphical abstract: Image 1 Highlights: Rheological measurements on bovine serum as artificial synovial fluid. A temperature dependence of density and viscosity could be verified. Shear-thinning characteristics could be demonstrated. An anomaly of pressure dependence of viscosity was found. This study emphasized the importance of realistic testing conditions for transferability.